2021
DOI: 10.1093/isp/ekab014
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ “Soft Skills” through the Flipped Classroom: Evidence from an International Studies Class

Abstract: The goal of this study is to evaluate the application of the flipped classroom (FC) format in the international studies curriculum. Previous research has examined the impact of the FC on students’ performance, operationalized by test scores, and demonstrated the utility of this technique in the learning process. Our research goes beyond student performance to evaluate the impact of the FC on student class attendance and the development of a set of soft skills, such as teamwork, critical thinking, self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Nevertheless, [50] show that the flipped classroom did not have a substantial impact on student performance, attendance, or soft skills, and according to [51] show that the flipped classroom has a small impact on student academic success.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, [50] show that the flipped classroom did not have a substantial impact on student performance, attendance, or soft skills, and according to [51] show that the flipped classroom has a small impact on student academic success.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research on flipped learning has shown several benefits of this format for students [20, 31], including creating space to practice professional skills, such as critical thinking [15, 59], self‐regulated and autonomous learning [21, 44], life‐long learning [36], and interpersonal skills [63]. However, conclusions in previous studies with regard to professional skill development in flipped learning environments were anecdotal, rather than being empirically tested [10]. This article aims to address this gap by empirically examining the development of teamwork skills in a flipped project management for civil engineering course.…”
Section: Related Workmentioning
confidence: 99%
“…Soft skills have then become very important in the education and instruction sector in recent years. In fact, it is possible to find in the specialized literature many designs of didactic methodologies specifically focused on soft skills work (Halimah and Sukmayadi, 2019;Betti et al, 2022). Among the soft skills of greatest formative interest are communication (Rohid et al, 2019) and teamwork skills (Nguyen et al, 2021), due to their transversal nature, since they are present in any work activity in today's globalized society.…”
Section: General Introductionmentioning
confidence: 99%